Managing Mental Accounts: Payment Cards and Consumption Expenditures - Gelman, Michael; Roussanov, Nikolai (Review of Financial Studies, 2024)
Abstract Does mental accounting matter for total consumption expenditures? We exploit a unique setting in which individuals exogenously receive a new payment card, without requesting one. Using random variation in the time of receipt, we show that individuals temporarily increase total consumption expenditure by making purchases with the new card without reducing spending on the others. We do not observe a corresponding increase in indebtedness. Total consumption expenditure rises even for the least liquidity-constrained individuals. The evidence is consistent with consumers treating methods of payment as nonfungible budget categories, as suggested by models of mental accounting and narrow bracketing.